Symbolic interaction and social media influence on junior athletes: a scoping review - Shodiq Hutomono; Teguh Santosa; Slamet Santoso; Widha Srianto; Fadli Ihsan (JRTI (Jurnal Riset Tindakan Indonesia), 2026)
Background Problems: Social media platforms are increasingly becoming a crucial component of junior athletes' daily lives, potentially shaping their athletic identity development and sporting performance. Research Objectives: The purpose of this systematic review was to carefully map and integrate the existing body of research on the impact of social media on junior athletes' sporting performance, with a particular focus on the process of identity formation as interpreted through the lens of symbolic interactionism theory. Methods: This scoping review followed PRISMA-ScR guidelines and searched five electronic databases (SciSpace, PubMed, Google Scholar, Web of Science, and Scopus) for studies published between 2005 and 2025. Findings from eligible studies were synthesized using a theory-informed thematic analysis guided by three core symbolic interactionist constructs: meaning construction, social interaction processes, and identity negotiation. Results: From an initial dataset of 122 records, 12 studies met the inclusion criteria established after the systematic review process. The included studies addressed three main themes: (1) Identity Construction and Self-Presentation – athletes actively engage in multifaceted identity formulation through social media platforms; (2) Peer Influence and Social Support - social media serves as a channel for constructive peer support and the emergence of performance-related anxiety; and (3) Performance Impact Mechanisms - there is a complex relationship between social media usage patterns and athletic performance outcomes. Conclusion: Current research indicates that social media significantly impacts junior athletes' identity formation and athletic performance through symbolic interaction processes. However, there are significant gaps in the literature, particularly regarding longitudinal studies, cross-cultural analyses, and intervention-focused research